1977
DOI: 10.1093/infdis/136.5.655
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Typing of Corynebacterium diphtheriae

Abstract: Bacteriophage types of over 3,000 strains of Corynebacterium diphtheriae isolated in Canada have been determined. The typing scheme used involved the use of nine phages. Results indicated that phage types correlate with biotypes to a large degree. Corynecin types were also determined for a limited number of cultures, and results indicated that the indicator strains presently available are unsuitable for the typing of C. diphtheriae strains isolated in North America. The distribution of phage types is similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Unlike diphtheria toxin, which occurs in about half of the isolates of C. diphtheria (Saragea et al, 1966;Toshach et al, 1977), PLD probably is characteristic of most or almost all strains of C. pseudotuberculosis and C. ulcerans and have not been found in any other Corynebacteria (Barksdale et al, 1981).…”
Section: Phospholipase D: Virulence Factormentioning
confidence: 99%
“…Unlike diphtheria toxin, which occurs in about half of the isolates of C. diphtheria (Saragea et al, 1966;Toshach et al, 1977), PLD probably is characteristic of most or almost all strains of C. pseudotuberculosis and C. ulcerans and have not been found in any other Corynebacteria (Barksdale et al, 1981).…”
Section: Phospholipase D: Virulence Factormentioning
confidence: 99%
“…Furthermore, ofthree strains of C. ulcerans similarly tested, one produced just detectable activity, and the others produced none. This cursory survey (data in column 1 of Table 2) suggested that PLD was no more peculiar to all strains of C. pseudotuberculosis and C. ulcerans than was diphtherial toxin peculiar to all strains of C. diphtheriae; the latter were found in only 50% of isolates during outbreaks of diphtheria (35,42). However, this preliminary Effects of the PLDs of C. pseudotuberculosis and of C. ulcerans which can be observed macroscopically on sheep blood agar plates.…”
Section: Discussionmentioning
confidence: 89%
“…We have employed these two systems for detecting PLD activity among a number of bacteria labeled as C. pseudotuberculosis and C. ulcerans and for ascertaining the distribution of PLD among representative species belonging to the genus Corynebacterium. Unlike diphtherial toxin, which occurs in only about 50% of field isolates of Corynebacterium diphtheriae (35,42), PLD appeared to be characteristic of most (if not all) strains of C. pseudotuberculosis and C. ulcerans, and it was not found in any other corynebacteria.…”
mentioning
confidence: 92%
“…Strains from Texas and adjacent states were examined by McCloskey, Saragea & Maximescu (1972), who found the majority of strains isolated during 1968-71 to belong to a previously undescribed intermedius type designated K, while most of the others belonged to gravis phage type XIV. In Canada, Toshach, Valentine & Sigurdson (1977) examined 3077 strains from Alberta with a limited set of the Saragea and Maximescu phages. Among the 1824 typable strains, 42 types were recognized but 20 of them were uncommon.…”
Section: Phage Typementioning
confidence: 99%